Reverse logistics: an analysis of construction retail sector - Pacito, Carolina Eduardo (2024)
The generation of solid waste constitutes a constant challenge resulting from the progress of society. Among the impactful sectors, construction stands out as one of the main contributors to environmental damage. In this context, the implementation of sustainable measures, such as reverse logistics, emerges as a tool to mitigate, manage, and treat this waste responsibly. This work seeks to identify the reverse logistics practices adopted in retail operations within the construction sector. To this end, an analysis was conducted based on semi-structured data and non-participative observations carried out in two construction retail stores in the Western Paulista region. The results reveal a underutilization of reverse logistics practices by companies, often due to a lack of knowledge or information on the part of the managers